Augmentation of alveolar part of mandible with CGF (concentrated growth factors) after multiple extractions – a case report - Gnatek, Adrian; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
Concentrated growth factors are one of platelet-rich plasma preparations (PPP), specially prepared in medical centrifuges. Due to high concentration of blood platelets, which reveal different sorts of growth factors, CGF stimulates wound healing, reduces post-operative complications, such as pain and swelling. The article presents a case of a 21-year-old-patient who underwent the augmentation of alveolar part of mandible with CGF after extractions of teeth 36, 37 and 38. The post-operative period, with follow-ups after one week and one-month post surgery, showed positive influence of applied plasma preparation